Exploring the pharmacological mechanism of Qufeng Tongluo Formula in the treatment of rheumatoid arthritis using network pharmacology methods and in vitro experimental validation - Man Lu; Jingjing He; Xinying Wang; Chunping Hu; Chenglei Zhao (Elsevier, 2023)
Background: Qufeng Tongluo Formula (QTF) is a clinical prescription for the treatment of rheumatoid arthritis. However, the mechanism and targets of action of QTF remain unclear. This study aims to uncover the pharmacological mechanism of QTF by employing a combination of network pharmacology and in vitro experimental validation. Methods: Multiple databases were searched to identify the targets of the ingredients present in Qufeng Tongluo Formula (QTF) and the targets associated with rheumatoid arthritis. The common targets between the component targets and disease targets were analyzed, and a visualization network representing the relationship between traditional Chinese medicine (TCM) components, diseases, and their targets was constructed. The STRING database was utilized to construct a protein-protein interaction (PPI) network of the common targets, and the CytoNCA plugin of Cytoscape software was utilized to identify the core targets. Metascape database was employed for GO and KEGG enrichment analysis of the common targets. The active ingredients of QTF and core targets were verified through molecular docking test. In vitro validation of the analysis results was performed using RA-FLS cells. Results: After data summarization and de-duplication, a total of 70 active ingredients and 994 targets were identified for QTF, while 4242 targets were associated with rheumatoid arthritis. Among them, 463 targets were found to be common to both. The PPI network screening identified AKT1, TNF, TP53, JUN, and INS as the core targets. GO analysis yielded a total of 4041 entries, with 3411 related to biological processes, 449 to molecular functions, and 181 to cellular components. The KEGG enrichment analysis primarily revealed significant involvement in signaling pathways such as Chemokine, NF-kappa B, Calcium, cAMP, and JAK-STAT. Kaurenoic acid, the active ingredient of the QTF, showed good results in molecular docking with the core targets. In vitro cellular experiments, QTF exhibited inhibition of proliferation, migration, and invasion of RA-FLS, while also reducing the release of inflammatory factors by blocking the activation of the TNF-α-induced NF-κB signaling pathway. Conclusions: This study conducted a comprehensive analysis of the targets and mechanisms that underlie the efficacy of QTF in the treatment of rheumatoid arthritis. Additionally, preliminary validation was achieved through in vitro experiments.